Enfermedades virales de la palma de aceite en el suroccidente colombiano y sus agentes causales - Morales, Francisco José; Lozano Potes, Iván; Arroyave, José A.; Castaño, M.; Sedano Cruz, RE; Velasco, Ana Cecilia (2002)
An investigation was initiated in 1998, to elucidate the etiology of two diseases of apparent viral nature in the southwestern African oil palm production region of Colombia. The ring spot disease was first observed in 1985, in the municipality of Tumaco, Nariño, causing a lethal disease of young (l-3 year-old) palms. Electron microscopy of diseased foliar tissue extracts revealed the presence of filamentous virus-like particles, ca. 800 nm in length. Double-stranded RNA ex tractions made from diseased palms, led to the cloning and partial sequencing of viral genome fragments showing amino acid sequence identities of 51-67% with the corresponding genes of the tentative foveavirus species Cherry green ringspot mottle virus and Cherry necrotic rusty mottle virus. Lower but consistent amino acid sequence identities (40-62%) were observed in comparisons with two recognized foveaviruses: Apple stem pitting virus and Rupestris stem pit ting-associated virus. The second disease, chlorotic ring , was first observed in 1996, also affecting young African oil palms in Tumaco. This disease is not lethal, but growers eliminate affected palms any way. The disease is caused by a different filamentous virus ca. 750 nm in length. The virus was characterized as a species of the genus Potyvirus, namely a strain of Sugarcane mosaic virus. Possible virus trans mission mechanisms and disease management practices are discussed here.